(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Most Iraqi economic units suffer from high rates of environmental pollution and a shortage of available resources and energy, which causes high production costs, in addition to the lack of these units in using modern cost techniques to determine and measure the quantities and costs of negative products, as well as reducing environmental impacts and the amount of emissions and waste, and exploiting available resources and energy in the form and production of products. Environmentally friendly, taking into account all economic and environmental aspects and improving environmental performance. One of these techniques is the material flow costing technique (ISO 14051 standard), Therefore, this research aims to explain the conceptual framework of the ISO 14051 standard for material flow costing technology and clarify its role in producing environmentally friendly products, preserving them, improving the quality of products, optimal exploitation of available resources and energy, and providing viable alternative solutions that would limit the loss of resources, and for the purpose of achieving the research goal and testing its hypothesis. The deductive approach was relied upon to build the research framework by reviewing the studies that dealt with the variables related to the research, and the inductive approach in completing the practical aspect of the research. The battery factory - Babylon 2 Laboratory was chosen and the financial and non-financial data included in the reports, records and documents for the year 2022 were approved and the data was collected and analyzed according to Material flow costing technology to improve the production process, One of the most important conclusions reached by the research is that using the ISO 14051 standard for material flow costing technology helps track inputs all the way to outputs, determines the quantity and cost of negative products, and helps management make improvements in order to reduce and limit them through optimal exploitation of resources, recycling, reducing waste and emissions, and reducing From environmental pollution.